Analisis Wacana Kritis Teun A Van Dijk Dalam Film Joko Widodo - Ramnaega Lisfariah Siregar; Syairal Fahmi Dalimunthe; M. Surip (EDUTECH, 2022)
Film as an audio-visual communication medium to convey a message to a group of people gathered in a certain place. As a media, many things can be conveyed to the public. One of them is the film "Joko Widodo". By using the critical discourse analysis of Teu A Van Dijk, the film "Joko Widodo" signifies an interpretation that tends to have the meaning of explaining the background of life and the way of politics of a Joko Widodo. This film tends to construct and create ideas so that the audience sees Jokowi as a leader who was born as a people and becomes a leader for the people. The reality of this film is included in the activities of a political campaign, because the film aims to build an image that you want to doctrine in the subconscious of the community. The reality of the film is built as a process of interaction with the community, so that it is not easily lost from the collective memory of the community. The reality of this film is not only made as a reflection of the character and appreciation in the life of a political figure, but this film is deliberately designed as a media for political campaigns.Keywords: Film, Critical Discourse Analysis, Teu A Van Dijk